Skip Navigation

7.2: The Logarithmic Derivative

Difficulty Level: At Grade Created by: CK-12
Turn In

This activity is intended to supplement Calculus, Chapter 6, Lesson 3.

Problem 1 – The Derivative of \begin{align*}y = \ln(x)\end{align*}y=ln(x)

If \begin{align*}(x, y)\end{align*}(x,y) is a point on \begin{align*}y = f(x)\end{align*}y=f(x) and \begin{align*}y = g(x)\end{align*}y=g(x) is the inverse of \begin{align*}f(x)\end{align*}f(x), then \begin{align*}(y, x)\end{align*}(y,x) is a point on \begin{align*}g(x)\end{align*}g(x). We know that \begin{align*}e^0 = 1\end{align*}e0=1 and \begin{align*}\ln(1) = 0\end{align*}ln(1)=0, so \begin{align*}(0, 1)\end{align*}(0,1) is a point on \begin{align*}y = e^x\end{align*}y=ex and \begin{align*}(1, 0)\end{align*}(1,0) is a point on \begin{align*}y = \ln(x)\end{align*}y=ln(x). We could do this for several points and keep getting the same inverse results.

Thus, if \begin{align*}y = e^x\end{align*}, then \begin{align*}x = e^y\end{align*} will be equivalent to \begin{align*}y = \ln(x)\end{align*} because they are inverses of one another. Now we can take the implicit derivative with respect to \begin{align*}x\end{align*} of \begin{align*}x = e^y\end{align*}.

\begin{align*}x=e^y \rightarrow 1 = \frac{dy}{dx} \cdot e^y \rightarrow 1 = \frac{dy}{dx} \cdot x \rightarrow \frac{1}{x} = \frac{dy}{dx}\end{align*}

Use the limit command to test this formula. Be careful with your parentheses.

  • Find \begin{align*}\lim_{h \to 0} \frac{\ln(2+h)- \ln(2)}{h}\end{align*}.
  • Do the same with \begin{align*}\lim_{h \to 0} \frac{\ln(3+h)- \ln(3)}{h}\end{align*}.
  • What is \begin{align*}\lim_{h \to 0} \frac{\ln(x+h)- \ln(x)}{h} ?\end{align*}

Use the derivative command to find the derivative of the logarithmic function \begin{align*}f(x) = \ln(x)\end{align*}.

Problem 2 – The Derivative of \begin{align*}y = \log_a(x)\end{align*}

What happens if our logarithm has a base other than \begin{align*}e\end{align*}? We need to know how to take the derivative of the function \begin{align*}y = \log_a(x)\end{align*}.

First we want to compare \begin{align*}y1 = \ln(x)\end{align*} and \begin{align*}y2 = \log_2(x)\end{align*}.

To enter \begin{align*}\log_2(x)\end{align*}, use the alpha keys to spell out log.

Within the parentheses, enter the expression, then the base.

  • Graph both functions (\begin{align*}\ln(x)\end{align*} and \begin{align*}\log_2(x)\end{align*}) on the same set of axes. Sketch your graph to the right. What do you notice?

  • Do the same steps with \begin{align*}y1 = \ln(x)\end{align*} and \begin{align*}y3 = \log_4(x)\end{align*}. What do you notice?

  • Simplify the following ratios.

\begin{align*}\frac{\ln(x)}{\log_2(x)} && \frac{\ln(x)}{\log_4(x)} && \frac{\ln(x)}{\log_a(x)}\end{align*}

Sometimes the ratio \begin{align*}\frac{\ln(x)}{\log_a(x)}\end{align*} is written as \begin{align*}\ln(x) = \ln(a) \cdot \log_a(x)\end{align*}. We can rewrite this ratio as \begin{align*}\log_a(x) = \frac{\ln(x)}{\ln(a)}\end{align*} and call it an identity.

  • Graph the following functions on the same set of axes: \begin{align*}y1 = \ln(x), y2 = \ln(2) \cdot \log_2(x), y3 = \ln(3) \cdot \log_3(x)\end{align*}. What was the result?

What happens when we take the derivative of \begin{align*}y = \log_a(x)\end{align*}. Use the derivative command to find the derivatives of the functions below.

\begin{align*}f(x) = \log_2(x) && g(x) = \log_3(x) && h(x) = \log_a(x)\end{align*}

  • Do you notice a pattern?

What does \begin{align*}\log_2(e)\end{align*} equal? If we use the formula from earlier in this class, we get \begin{align*}\log_2(e) = \frac{\ln(e)}{\ln(2)} = \frac{1}{\ln(2)}\end{align*}.

Therefore, the general result is \begin{align*}y = \log_a(x) \rightarrow \frac{dy}{dx} = \frac{1}{(x \ln(a))}\end{align*}.

Problem 3 – Derivative of Exponential and Logarithmic Functions Using the Chain Rule

Now we want to take the derivative of more complicated functions:

Recall: \begin{align*}y = a^u \rightarrow \frac{dy}{dx} = a^u \ \frac{du}{dx}\end{align*} where \begin{align*}u\end{align*} depends on \begin{align*}x\end{align*}.

  • Suppose that \begin{align*}y = \log_a(u)\end{align*}, where \begin{align*}u\end{align*} depends on \begin{align*}x\end{align*}. Using the chain rule, take the derivative of this function.

Find the derivative of the following functions with the chain rule.

Identify \begin{align*}u(x)\end{align*} and \begin{align*}a\end{align*} for each function before you find the derivative.

  • \begin{align*}f(x) = 5^{(x^2)} \quad u(x)=\underline{\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;} \quad a =\underline{\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;}\end{align*}

\begin{align*}f'(x) = \underline{\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;}\end{align*}

  • \begin{align*}g(x) = e^{(x^3+2)} \quad u(x)=\underline{\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;} \quad a = \underline{\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;}\end{align*}

\begin{align*}g'(x) = \underline{\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;}\end{align*}

  • \begin{align*}h(x) = \log_3(x^4 + 7) \quad u(x)=\underline{\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;} \quad a =\underline{\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;}\end{align*}

\begin{align*}h'(x) =\underline{\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;}\end{align*}

  • \begin{align*}j(x) = \ln \left (\sqrt{x^6 + 2} \right ) \quad u(x)=\underline{\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;} \quad a = \underline{\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;}\end{align*}

\begin{align*}j'(x) =\underline{\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;\;}\end{align*}

Notes/Highlights Having trouble? Report an issue.

Color Highlighted Text Notes
Show More

Image Attributions

Show Hide Details
Date Created:
Feb 23, 2012
Last Modified:
Nov 04, 2014
Save or share your relevant files like activites, homework and worksheet.
To add resources, you must be the owner of the section. Click Customize to make your own copy.
Please wait...
Please wait...
Image Detail
Sizes: Medium | Original